Nature and mindfulness to cope with work-related stress: A narrative review - Menardo, E.; Di Marco, D.; Ramos, S.; Brondino, M.; Arenas, A.; Costa, P.; Carvalho, C. V. de; Pasini, M. (International Journal of Environmental Research and Public Health, 2022)
In recent years, work-related stress has grown exponentially and the negative impact that this condition has on people’s health is considerable. The effects of work-related stress can be distinguished in those that affect workers (e.g., depression and anxiety) and those that affect the company (e.g., absenteeism and productivity). It is possible to distinguish two types of prevention interventions. Individual interventions aim at promoting coping and individual resilience strategies with the aim of modifying cognitive assessments of the potential stressor, thus reducing its negative impact on health. Mindfulness techniques have been found to be effective stress management tools that are also useful in dealing with stressful events in the workplace. Organizational interventions modify the risk factors connected to the context and content of the work. It was found that a restorative workplace (i.e., with natural elements) reduces stress and fatigue, improving work performance. Furthermore, practicing mindfulness in nature helps to improve the feeling of wellbeing and to relieve stress. In this paper, we review the role of mindfulness-based practices and of contact with nature in coping with stressful situations at work, and we propose a model of coping with work-related stress by using mindfulness in nature-based practices.